Pembuatan Dan Pemanfaatan Electric Wheelchair Bagi Penyandang Disabilitas Di RT.36 Kelurahan Telagasari - Frans Ivan Christofel Hutabarat; Gad Gunawan; Alfian Djafar; Rijal Surya Rahmany; Andre Amba Matarru; I Made Ivan Wiyarta Cakra Sujana; Yongki Christandi Batubara; Kevin Hasiholan Lumban Tobing; Razif Mahmudi Syahlie; Linda; Yonathan Parsaulian Lobo Silalahi; Rifqi Al Wafi; Bagas Hendi Prasetya (CV. Multi Kreasi Media, 2024)
Currently, there are individuals around us living with disabilities caused by accidents or other factors. People with disabilities generally require assistance from others, particularly for mobility or moving from one place to another. Although manual wheelchairs can provide a solution for mobility, they remain challenging to operate using hand power alone and often require external help for movement. To facilitate mobility for individuals with disabilities, especially wheelchair users, an electric drive system in the form of an electric motor is proposed as a solution. The development of a motorized electric wheelchair aims to enhance the mobility of individuals with physical disabilities. Members of the Indonesian Association of Persons with Disabilities (PPID) were selected as community service partners for this initiative. It is hoped that, in addition to supporting mobility, the electric wheelchair can also serve as a body support system, enabling users to continue engaging in productive activities while seated. The implementation of this program began with interviews conducted with persons with disabilities and related partners to understand their needs, followed by the design, fabrication, and subsequent socialization and training on the use of the electric wheelchair for the target beneficiaries. The outcome of this effort is an electric wheelchair equipped with joystick controls. The wheelchair employs a rear-wheel drive system powered by two motors, each attached to a rear wheel, and a chain transmission system. Along with delivering the electric wheelchair to the PPID, this initiative aims to serve as a practical application of mechanical engineering knowledge, directly benefiting the community..